2010
DOI: 10.1158/0008-5472.sabcs10-p5-10-15
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P5-10-15: First Safety Data from a Randomised Phase III (CIBOMA 2004- 01/GEICAM 2003-11) Trial Assessing Adjuvant Capecitabine Maintenance Therapy after Standard Chemotherapy for Triple-Negative Early Breast Cancer

Abstract: Background: A large adjuvant trial programme is exploring the role of capecitabine (C) in early breast cancer (EBC). CIBOMA 2004-01/GEICAM 2003-11 is a multicenter, international randomised phase III trial that focuses on adjuvant C maintenance therapy after conventional induction chemotherapy in triple-negative EBC. Here we report interim safety data from the trial. Materials and methods: Patients (pts) with operable, node-positive (or node-negative with tumour diameter ≥1 cm), hormone receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The primary endpoint was DFS. The first safety data, presented at the 2010 San Antonio Cancer Symposium [22], revealed that the safety profile of adjuvant X as maintenance therapy was consistent with its known toxicity profile. More than 75% of patients were able to continue their treatment as planned with approximately 15% discontinuing due to toxicity or withdrawal.…”
Section: Duration Of Adjuvant Chemotherapy In Tnbcmentioning
confidence: 92%
“…The primary endpoint was DFS. The first safety data, presented at the 2010 San Antonio Cancer Symposium [22], revealed that the safety profile of adjuvant X as maintenance therapy was consistent with its known toxicity profile. More than 75% of patients were able to continue their treatment as planned with approximately 15% discontinuing due to toxicity or withdrawal.…”
Section: Duration Of Adjuvant Chemotherapy In Tnbcmentioning
confidence: 92%
“…The first safety data from the randomized phase III (CIBOMA 2004-01/GEICAM 2003-11) trial were published by Lluch et al in San Antonio cancer symposium 2010 revealing that more than 75% of patients were able to continue their treatment as planned with approximately 15% of patients discontinuing due to toxicity or withdrawal. Grade 3 or 4 adverse effects were higher in extended adjuvant capecitabine treatment, hand foot syndrome 17.4%, diarrhea 2.9%, vomiting 1.0%, and elevated bilirubin 1.0% [41]. This preliminary safety analyses on 405 patients reported 7 serious adverse events considered possibly related to capecitabine (hospitalization for grade 2-4 diarrhea in 3 patients; grade 2 thoracic pain, grade 2 arrhythmia, coronary vasospasm and chest pain in 1 patient each) [14].…”
Section: Discussionmentioning
confidence: 84%
“…There are several ongoing studies that include phase III trials which explore the addition of capecitabine to standard adjuvant chemotherapy, or through introduction of maintenance therapy [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup analysis of a few trials performed in advanced disease have suggested lack of activity [43,44], [47]. Accrual (876 patients) has been completed and final results are eagerly awaited, as this is one of the first adjuvant studies specifically targeting this subtype of EBC patients.…”
Section: Capecitabine In Triple-negative Breast Cancer Patientsmentioning
confidence: 99%